2011
DOI: 10.1152/ajplung.00176.2011
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2protects murine lungs from bleomycin-induced pulmonary fibrosis and lung dysfunction

Abstract: Prostaglandin E(2) (PGE(2)) is a lipid mediator that is produced via the metabolism of arachidonic acid by cyclooxygenase enzymes. In the lung, PGE(2) acts as an anti-inflammatory factor and plays an important role in tissue repair processes. Although several studies have examined the role of PGE(2) in the pathogenesis of pulmonary fibrosis in rodents, results have generally been conflicting, and few studies have examined the therapeutic effects of PGE(2) on the accompanying lung dysfunction. In this study, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 58 publications
6
65
2
1
Order By: Relevance
“…Furthermore, the antifibrotic effect of noscapine in our experiments ( Fig. 1) was similar to that shown for PGE 2 , also in the bleomycin model (16). Of note, multiple groups have demonstrated dysregulation of PGE 2 synthesis (as a result of down-regulation of COX-II expression) in the lung of human patients with pulmonary fibrosis as well as in animal models, which was associated with severity of the disease (42)(43)(44)(45)(46)(47), suggesting that activation of PGE 2 receptors could be an attractive approach for treatment of pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the antifibrotic effect of noscapine in our experiments ( Fig. 1) was similar to that shown for PGE 2 , also in the bleomycin model (16). Of note, multiple groups have demonstrated dysregulation of PGE 2 synthesis (as a result of down-regulation of COX-II expression) in the lung of human patients with pulmonary fibrosis as well as in animal models, which was associated with severity of the disease (42)(43)(44)(45)(46)(47), suggesting that activation of PGE 2 receptors could be an attractive approach for treatment of pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies using the bleomycin model of pulmonary fibrosis have shown the protective effects of the prostacyclin analog iloprost or of prostaglandin E 2 (15,16), both of which are known to act through cAMP/PKA signaling. We have shown a similar protective effect of adrenomedullin in a mouse model with genetic sensitization of adrenomedullin signaling in myofibroblasts (17).…”
mentioning
confidence: 99%
“…23 Fibrosis is thought to be a result of cellular damage initiating an inflammatory response and activation of lung fibroblasts, and thus inhibition or modulation of proliferative signaling (such as TGF-b, HGF, tyrosine kinase, PDGF or PGE 2 , 9,10,24,25 which is in accordance with the increased proliferation and number of myofibroblasts presented in this paper. The specific signaling pathways of this model are still unknown, but most likely mimics the ones previously described.…”
Section: Discussionsupporting
confidence: 64%
“…63 However, PGE2, when administered to mice 14 days after bleomycin, failed to provide significant therapeutic effects on lung function or fibrosis. 64 Nuclear factor erythroid 2-related factor 2 (NRF2) is regarded as a master regulator of cellular resistance to oxidants and regulates expression of genes, limiting the inflammatory and fibrotic responses. 39 In primary IPF and normal lung fibroblasts, siRNA activation of NRF2 by either Keap1 siRNA or sulforaphane induced myofibroblast dedifferentiation with down-regulation of a-SMA, along with reduced cell proliferation, migration, and contraction, and was associated with restored oxidant/antioxidant balance in the cells.…”
Section: Role Of Dedifferentiation In Removing Myofibroblastsmentioning
confidence: 99%